Ablation behaviour of carbon fibre ultra-high temperature composites at oblique angles of attack. (15th December 2021) - Baker, B.; Venkatachalam, V.; Zoli, L.; Vinci, A.; Failla, S.; Sciti, D.; Binner, J.
Graphical abstract: Highlights: Angled torch testing of ceramic composites at 90-10° doubled surface shear stress. Low angles reduced incident surface pressure by 85%. Surface temperatures decreased by 15% at reduced incident angles. Damage area and oxide microstructure reduced commensurately with temperature. The aerodynamic flow regime modified oxidation behaviour significantly Abstract: Oxyacetylene torch testing was performed at a range of angles of attack on Cf /ZrB2 -SiC-Y2 O3 composites, from 10° to 90°. The ablation behaviour was studied in-situ with thermography, and the post-ablation morphologies investigated optically and with elemental analysis. Significantly lower surface temperatures were observed at oblique angles of attack leading to less damage in terms of both oxidation extent and material removal. Rudimentary modelling of a gas stream impinging on a perfect surface showed that the angular variation also led to a significant drop in pressure at more oblique angles of attack, with a commensurate increase in shear stress. The surface oxide formed during testing seemed mainly to correspond to the temperature distribution and was apparently more susceptible to damage from higher impinging pressure than shear stress. This study elucidated some interesting aspects of a modified ablation test and showed some new parameter ranges which may be useful in targeted material screening.